The Determinants of Internet Banking Adoption by UUM Students - Al Gaifi, Fadhel Mohammed Abdullah (2011)
Two hundred and eighty six questionnaires, which are considered as complete, acceptable and usable, were received from the students of UUM. Questionnaires are developed to examine the major factors considered most important in the process of adopting internet banking by students in UUM. In other words, this study aims to define the major determinants of internet banking adoption by students inside UUM. The data are analyzed by using SPSS programme. Descriptive and correlation analysis have been applied to determine the significant relationships for all hypotheses at 1 percent level of significance. In addition, factor analysis has also been used to inspect how variables affect each other and to what extent they are interrelated. The findings reveal that all independent variables included in this study namely “Perceived Ease of Use (PEU)”, “Perceived Usefulness (PU)”, “Perceived Web Security (PWS)” and “Attitude (AT)” have a significant relationship with the dependent variable which is “Intention to Use internet banking (IU)”. We also find that there is a significant relationship among independent variables. Percentage and frequency distribution are also used to analyze the respondent’s profile.